The potential role of variations in juvenile hip geometry on the development of Legg-Calvé-Perthes disease: a biomechanical investigation. Issue 2 (25th January 2018) - Pinheiro, Manuel da Silva; Dobson, Catherine; Clarke, Nicholas M.; Fagan, Michael
Abstract: Legg-Calvé-Perthes disease (LCP) is one of the most poorly understood diseases in paediatric orthopaedics. One common trait of LCP is the marked morphological difference between healthy and pathological hips, early deviations of which (i.e. prior to disease onset) have been suggested to lead to the overload and collapse of the epiphysis. Here, the impact of common variations in geometry is investigated with a finite element model of a juvenile femur under single leg standing and landing. Here, the impact of typical variations in geometry is investigated with a finite element model of a juvenile femur under single leg standing and landing. The variations appear to have only a limited effect on the stress distribution in the femoral epiphysis even during high impact activities. This suggests that, for this individual at least, they would be unlikely to cause epiphyseal overload and collapse, even in the presence of a skeletally immature epiphysis.